2021
DOI: 10.1111/icad.12483
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biotic factors driving the diversity of spider assemblages in tree hollows of MediterraneanQuercusforests

Abstract: Tree hollows are keystone structures that promote forest biodiversity. This study analyses the spatio‐temporal diversity of spiders in these microhabitats. Forty‐eight emergence traps were installed in tree cavities of Quercus pyrenaica forests in the Iberian Peninsula. Traps were collected monthly during a complete year. Generalised linear models and canonical correspondence analysis were used to evaluate the effect of two physical (hollow volume and height above ground) and three biotic variables (beetle ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In fact, recent studies conducted with predatory arthropods (Coleoptera and Odonata) in tree hollows show that communities segregate as a consequence of habitat preferences rather than competition (Oliveira-Junior et al, 2021;Sánchez-Galván et al, 2018). Moreover, knowing that hollows are physically and chemically heterogeneous from one another (Mic o et al, 2015) and that the Order Araneae is a very sensitive group to variations in environmental conditions (Jiménez-Valverde & Lobo, 2007;Košulič et al, 2016;Malumbres-Olarte et al, 2018;Müller et al, 2020), it is understandable that spiders are distributed in these saproxylic microenvironments according to their ecological preferences (Hernández-Corral et al, 2021). For instance, in the H. gredensis-T. denticulata pair (Tables 2 and 3), the former species prefers humid environments (Bidegaray-Batista et al, 2014) and requires little space for hunting (Hernández-Corral et al, 2021), while the latter species is usually found in sunny environments (Hernández-Corral, 2020) and needs larger spaces to build its hunting webs (Hernández-Corral et al, 2021).…”
Section: Spatio-temporal Aggregations Do Not Rule Out Interspecific C...mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent studies conducted with predatory arthropods (Coleoptera and Odonata) in tree hollows show that communities segregate as a consequence of habitat preferences rather than competition (Oliveira-Junior et al, 2021;Sánchez-Galván et al, 2018). Moreover, knowing that hollows are physically and chemically heterogeneous from one another (Mic o et al, 2015) and that the Order Araneae is a very sensitive group to variations in environmental conditions (Jiménez-Valverde & Lobo, 2007;Košulič et al, 2016;Malumbres-Olarte et al, 2018;Müller et al, 2020), it is understandable that spiders are distributed in these saproxylic microenvironments according to their ecological preferences (Hernández-Corral et al, 2021). For instance, in the H. gredensis-T. denticulata pair (Tables 2 and 3), the former species prefers humid environments (Bidegaray-Batista et al, 2014) and requires little space for hunting (Hernández-Corral et al, 2021), while the latter species is usually found in sunny environments (Hernández-Corral, 2020) and needs larger spaces to build its hunting webs (Hernández-Corral et al, 2021).…”
Section: Spatio-temporal Aggregations Do Not Rule Out Interspecific C...mentioning
confidence: 99%
“…Moreover, knowing that hollows are physically and chemically heterogeneous from one another (Mic o et al, 2015) and that the Order Araneae is a very sensitive group to variations in environmental conditions (Jiménez-Valverde & Lobo, 2007;Košulič et al, 2016;Malumbres-Olarte et al, 2018;Müller et al, 2020), it is understandable that spiders are distributed in these saproxylic microenvironments according to their ecological preferences (Hernández-Corral et al, 2021). For instance, in the H. gredensis-T. denticulata pair (Tables 2 and 3), the former species prefers humid environments (Bidegaray-Batista et al, 2014) and requires little space for hunting (Hernández-Corral et al, 2021), while the latter species is usually found in sunny environments (Hernández-Corral, 2020) and needs larger spaces to build its hunting webs (Hernández-Corral et al, 2021). Likewise in the E. atrica-T. denticulata segregation (Table 2 and Figure 2l), the difference in their sizes may mean that they prefer larger or smaller hollows, respectively.…”
Section: Spatio-temporal Aggregations Do Not Rule Out Interspecific C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the different types and characteristics of each microhabitat constrain species' functional traits and trophic guild distribution (Micó et al, 2020), which means that their presence and heterogeneity drive species diversity in different ways. Tree management (i.e., pollarding) promotes tree hollow formation, which are keystone elements for forest diversity, especially for arthropods (Müller et al, 2013;Micó, 2018;Hernández-Corral et al, 2021). The presence of tree hollows favours species richness, and doubling the mean number of tree hollows per hectare (from 10 to 20 trees) has been reported to increase species richness by more than 7%.…”
Section: Tree Microhabitats Are Key For Beetle Taxonomic Diversity An...mentioning
confidence: 99%
“…One of the most interesting communities for studying insect dispersal behaviour within forest ecosystems are the saproxylic assemblages that inhabit tree hollows. 1 First, tree hollows are considered a keystone microhabitat for European forest biodiversity conservation [ 16 18 ]. Second, cavity availability and spatial connectivity are currently jeopardized by several factors, such as forest fragmentation, climatic change, forestry and the abandonment of cultural practices such as tree pollarding (note that tree pollarding accelerates the formation of tree cavities) [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%